Classroom Management Practices and Student Performance in Architectural Drafting Technology - Cariza Flores (MASI Mandiri Edukasi, 2025)
Effective classroom management is crucial in technical education, particularly in disciplines like Architectural Drafting Technology (ADT), where discipline and practicality play significant roles in student learning. This study assessed specific classroom management practices relative to student performance and participation in the 2024-2025 Bachelor of Science in Industrial Technology program, majoring in ADT. A survey design was selected, and purposive sampling was chosen to choose respondents from varied year levels. The quantitative analysis consisted of descriptive statistics, correlation coefficients via Pearson, and linear regression to determine relationships between the management practices illustrated under the study and the academic variables. The study clarified how active supervision, policies, technology, and positive reinforcement positively affect students’ performance, attendance, and behavior. More explicitly, engaging and systematic tasks of limited conceptual density are conducive to learning gains, while interchange and the reduction of off-task behavior are promoted by employing technological supports. These findings indicate that adequate classroom management, proactively organized and preventive-descriptive, should be considered and applied correctly in technical education contexts. Teachers are encouraged to prepare to integrate these strategies in their classrooms effectively; the study suggests further research to establish its long-term result on skills acquisition and achievements.